Empirical phenotyping and genome-wide association study reveal the association of panicle architecture with yield in Chenopodium quinoa - Habib, Zakia; Ijaz, Siddra; Haq, Imran Ul; Hashem, Abeer; Avila-Quezada, Graciela Dolores; Abd_Allah, Elsayed Fathi; Khan, Nasir Ahmad (Frontiers in Microbiology, 2024)
Chenopodium quinoa manifests adaptability to grow under varying agro-climatic scenarios. Assessing quinoa germplasm's phenotypic and genetic variability is a prerequisite for introducing it as a potential candidate in cropping systems. Adaptability is the basic outcome of ecological genomics of crop plants. Adaptive variation predicted with a genome-wide association study provides a valuable basis for marker-assisted breeding. Hence, a panel of seventy-two quinoa plants was phenotyped for agro morphological attributes and association-mapping for distinct imperative agronomic traits. ISSR markers were employed to assess genetic relatedness and population structure. Heatmap analysis showed three genotypes were early maturing, and six genotypes were attributed for highest yield. The SD-121-07 exhibited highest yield per plant possessing green, glomerulate shaped, compact density panicle with less leaves. However, SJrecm-03 yielded less exhibiting pink, intermediate shape, intermediate density panicles with less leaves. The phenotyping revealed strong correlation of panicle architecture with yield in quinoa. A genome-wide association study unraveled the associations between ISSR makers and agro-morphological traits. MLM analysis yielded nine markers associated with eight traits at p ≤ 0.01. Moreover, ISSR markers significantly associated with panicle shape and leafiness were also associated with yield per plant. These findings contribute to the provision of authenticity for marker-assisted selection that ultimately would support quinoa breeding programs.